1997
DOI: 10.1017/s0890037x00041361
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Glufosinate on Rice (Oryza sativa) Transformed with the BAR Gene and Red Rice (Oryza sativa)

Abstract: Glufosinate at 1.1 and 2.2 kg/ha injured ‘Koshihikari’ rice lines that were transformed with the BAR gene from 0 to 53%. However, transgenic ‘Gulfmont’ rice was not injured. Rice yields of transgenic ‘Gulfmont’ lines and six of nine ‘Koshihikari’ lines were not affected by 2.2 kg/ha glufosinate. In field studies, flooding reduced the efficacy of glufosinate in controlling red rice, and greenhouse tests determined that glufosinate efficacy was reduced when red rice was submerged between 25 and 50% of its height… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0
1

Year Published

1999
1999
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 14 publications
1
13
0
1
Order By: Relevance
“…1992). Sankula et al (1997a) reported that glufosinate at 1.1 kglha caused minimal injury to BAR-transformed rice (Oryza sativa L.) compared to nontransformed rice. In addition, yield of transgenic rice was not affected (Sankula et a1.…”
Section: Introductionmentioning
confidence: 99%
“…1992). Sankula et al (1997a) reported that glufosinate at 1.1 kglha caused minimal injury to BAR-transformed rice (Oryza sativa L.) compared to nontransformed rice. In addition, yield of transgenic rice was not affected (Sankula et a1.…”
Section: Introductionmentioning
confidence: 99%
“…Under greenhouse conditions, glufosinate efficacy was reduced when weedy rice was submerged between 25% and 50% of its height. Height and dry weight of weedy rice plants increased as flood water depth increased regardless of glufosinate dose (Sankula et al, 1997a). Interestingly, in this study Gulfmont transgenic rice was not affected by glufosinate, while 'Koshihikari' lines were injured as much as 53%.…”
Section: Herbicide-resistant Rice and Weed Managementmentioning
confidence: 45%
“…Glufosinate damage to resistant rice is growth-stage dependent, usually being more toxic to younger plants but even late applications, when the crop is more tolerant, still resulted in a 16% yield penalty (Sankula, Braverman & Linscombe, 1997c;Griffin, Linscombe & Zhang, 1999). At the three-to four-leaf stage, injury to weedy rice was up to 11 times higher than the injury caused to the resistant cultivar (Sankula et al, 1997a). Glufosinate toxicity to transgenic rice also increased when it was applied in combination with either triclopyr or acifluorfen.…”
Section: Herbicide-resistant Rice and Weed Managementmentioning
confidence: 95%
“…O grau de prejuízo causado pelo arroz vermelho é atribuído a sua habilidade competitiva com o arroz cultivado, podendo causar redução de até 82% no rendimento, segundo Sankula et al (1997). Contudo, neste trabalho a redução de produtividade foi cerca de 95%, em função da elevada população que se estabeleceu na área experimental no segundo ano de pesquisa.…”
Section: Resultsunclassified